Household Energy Infrastructure, Cooking Fuel Use, and Mental Health Among Older Adults in Rural China - You‐hua Wang; Rui Liu; Ming‐yang Chen; Zi‐xuan Xiong; Yue Li (International Journal of Geriatric Psychiatry, 2026)
ABSTRACT Objectives To compare the associations of household energy infrastructure and primary cooking fuel use with mental health among older adults in rural China. Methods This cross‐sectional analysis included 4975 rural adults aged 60 years or older from 3291 households in the 2018 China Health and Retirement Longitudinal Study. Mental health was operationalized as depressive symptoms measured using the 10‐item Center for Epidemiologic Studies Depression Scale (CESD‐10); the continuous score was primary and CESD‐10 ≥ 10 secondary. Exposures were Coal gas/natural gas availability, heating availability, and primary cooking fuel (solid, gaseous, or electric). Separate adjusted linear and logistic regression models used household‐clustered standard errors. Results Neither Coal gas/natural gas availability ( b = −0.249, 95% CI −0.850 to 0.353; p = 0.418) nor heating availability ( b = 0.104, 95% CI −0.811 to 1.018; p = 0.824) was clearly associated with CESD‐10 scores. Compared with solid fuel, gaseous fuel ( b = −1.422, 95% CI −1.889 to −0.956; p < 0.001; OR = 0.663, 95% CI 0.569–0.771) and electricity ( b = −0.631, 95% CI −1.150 to −0.113; p = 0.017; OR = 0.851, 95% CI 0.727–0.996) were associated with lower scores and lower odds of probable depressive symptoms. Findings were consistent across sensitivity analyses. Conclusions Primary use of gaseous or electric cooking fuel was associated with better mental health, reflected in fewer depressive symptoms, whereas neither infrastructure indicator showed a clear association. Nominal availability and routine use should be measured separately. Longitudinal evidence is needed before causal conclusions can be drawn.